2016
DOI: 10.11604/pamj.2016.24.66.8771
|View full text |Cite
|
Sign up to set email alerts
|

Toxicological assessment of the hydroethanolic leaf extract of clerodendrum capitatum in wistar rats

Abstract: IntroductionClerodendrum capitatum (Willd) Schumach. & Thonn (Lamiaceae) is used in African traditional medicine for the treatment of malaria, hypertension, obesity, jaundice and diabetes however there is lack of experimental data on its possible toxicity. This study investigated the acute and 28 days sub-chronic toxicity of C. capitatum in Wistar rats.MethodsIn acute toxicity tests, a single administration of the hydroethanolic C. capitatum leaf extract (5 g/kg) was given orally to 5 female rats. The general … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
16
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(21 citation statements)
references
References 28 publications
4
16
1
Order By: Relevance
“…Our results demonstrated that repeated administration of CuAE did not induce significant side effects on the weight of vital organs. Our results are in accordance with those of many authors who found that the chronic administration of C. infortunatum leaves methanolic extract as well as C. capitatum did not affect the weight of vital organs [14,16].…”
Section: Test Groups Satellite Groupssupporting
confidence: 93%
See 3 more Smart Citations
“…Our results demonstrated that repeated administration of CuAE did not induce significant side effects on the weight of vital organs. Our results are in accordance with those of many authors who found that the chronic administration of C. infortunatum leaves methanolic extract as well as C. capitatum did not affect the weight of vital organs [14,16].…”
Section: Test Groups Satellite Groupssupporting
confidence: 93%
“…Organ-to-body weight is an important index to diagnose whether an organ has been exposed to injury. Hence, if mice are exposed to toxic substances, the weight of the damaged organ will either increase or decrease as will the organto-body weight ratio [16,20]. Our results demonstrated that repeated administration of CuAE did not induce significant side effects on the weight of vital organs.…”
Section: Test Groups Satellite Groupsmentioning
confidence: 60%
See 2 more Smart Citations
“…The universal distribution of AST in the cytoplasmic pool of tissues like liver, kidney, heart, muscles, spleen and others with much amount in their mitochondria gave a disparity in relation to ALT, whose activity is strictly localized in the cytoplasm of hepatocyte (Abel and Banjo, 2012;Akhigbe, 2014;Magnifouet et al, 2011;Mezui et al, 2015;York, 2017). This resulted in the application of ALT activity as a definite biomarker for hepatocellular injury while AST activity may not be adequate as a lone biomarker for hepatocellular injury, except employed together (Idoh et al, 2016;Ogbe et al, 2012;York, 2017). Again, ALP activity, which is primarily localized in membranes of osteoblastic cells of bones, mammary gland, placental, intestinal mucosa, renal proximal tubules and hepatocytes, where it functions in the alkaline hydrolysis of organophosphates to maintain biological membrane integrity.…”
Section: Resultsmentioning
confidence: 99%